Controlled Magnetic wedge Linear Adjustable Reactor - GUAN Rui yang; WEI Xin lao; ZHU Bo; XUE Zhi chao (Journal of Harbin University of Science and Technology)
This paper proposed a reactor whose inductance adjustment was based on a controlled magneticwedge By adjusting the depth of controlled magneticwedge inserted to change the equivalent airgap in magnetic path which could lead to inductance value adjusted continuously, reactor’s working principles in 3 conditions were analyzed in detail and inductance’s mathematical models were provided ANSYS was used to simulate the magnetic field in order to verify the analysis previously An experimental prototype and magneticwedge controlling system were made in order to measure inductance adjustment curve Simulations and experimental results confirmed the correctness of this reactor’s theory Results showed that inductance’s adjustment curve was a piecewise function, when magneticwedge was in positive section, the relationship between inductance and depth of magneticwedge inserted was a linear function, if magneticwedge was totally inserted, the inductance was maximum, if magneticwedge was totally pulled out, the inductance was minimum When magneticwedge was in negative section, the relationship between inductance and position of magneticwedge was a doubleexponential function, the nearer magneticwedge’s position was, the more sensitively inductance changed The range of inductance adjustment in positive section was 20 times as large as that in negative section The controlled magneticwedge could adjust inductance widely and quickly in positive section, while it could only finetune the inductance in negative section Magneticwedge could control magnetic path and restrain airgap edge effect